Suffered life, hard life: adverse experiences in childhood of people with chronic musculoskeletal pain - Cleiber Henrique Borini; Diene Monique Carlos; Lazslo Antônio Ávila; Simone Saltareli; Priscilla Hortense
ABSTRACT Objective: To analyze the adverse experiences lived in the childhood by people with chronic musculoskeletal pain, based on psychoanalytic psychosomatics. Methods: Qualitative research, developed with 20 people with chronic musculoskeletal pain and who were receiving physiotherapeutic treatment at a clinic in the countryside of the state of São Paulo. The data were collected during the months of June and July 2018, through semi-structured interviews. This article refers to one of the resulting themes of reflexive thematic analysis: Suffered life, hard life. Results: When talking about their lives, people living with chronic musculoskeletal pain revealed themes associated with some adverse childhood experiences such as parental deaths, neglect, economic hardship, family violence, physical and psychological violence. Final considerations: The analysis of adverse experiences lived in childhood by people with chronic musculoskeletal pain shows presence of intense suffering revealed in people's speech when associated with perceived physical pain.